Hubungan Kehamilan Usia Remaja dengan Kelahiran Prematur di RSUD Cengkareng Jakarta Barat Tahun 2022: Sebuah Studi Kohort Retrospektif - Triana, Anna; Ronoatmodjo, Sudarto (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Premature birth is leading causes of neonatal mortality. According to the World Health Organization (WHO), global premature birth rates reached 9.9% in 2020, it’s rising compared to preterm birth rates in 2010. One of the risk factors for preterm birth is the mother's age, which pregnant adolescents are more at risk of giving birth to preterm babies due to physiological, psychological, and socioeconomic immaturity. This study is an analytical study with a retrospective cohort design to determine the relationship between adolescents pregnancy and preterm birth. This study was conducted in Cengkareng General Hospital West Jakarta using patient’s medical record data. The population in this study were all pregnant women who were admitted to the hospital with signs of labor in the period of 1st January 2022 until 31st December 2022. Sampling was carried out using simple random sampling technique with a total of 141 respondents in each group of respondents who experienced adolescent pregnancies (10-19 years) as the exposed groups and the group of respondents who experienced pregnancies in healthy reproductive age (20-34 years) as the non-exposed groups. Data were analyzed using cox regression test. The analysis revealed that adolescent pregnancy increased the risk of premature birth by 3.57 times (RR adj= 3,57; 95%CI: 2,06-6,20; p= 0,000) after controlling for maternal education, occupation, marital status, gestational hypertension, and anemia. Keywords: Premature birth, preterm birth, adolescents pregnancy